HUBUNGAN GANGGUAN PROSES MAKAN DENGAN PICKY EATER PADA ANAK BALITA - Dwi Herman Susilo (Oksitosin : Jurnal Ilmiah Kebidanan, 2016)
Trouble eating disorders in children often encountered in ordinary people who do not understand the procedures fulfilling the nutritional needs of children. Ordinary people are still many who do not understand the importance of nutrition in children. According to the preliminary results of a study conducted by researchers in Pustu Mimbaan II with number 148 Toddlers, there are 108 people who have difficulty eating. This study aims to analyze the relationship between eating disorders with a difficult process of eating. This study was observational analytic study with cross sectional analytic design with a sample of mothers who have children in sub Mimbaan II Panji Situbondo. The sample size amount 108 people. Data were collected by using a questionnaire. The data obtained were tested using the chi-square. From the calculation of research data used Chi Square test on highest level (α = 0.05) obtained the results of the 0081, then H0 was accepted and H1 was rejected which means that there was a relationship of interference with the process of feeding a picky eater (hard to eat). Keywords : Process of Eating disorders and Picky Eater. ABSTRAK Masyarakat awam masih banyak yang belum memahami pentingnya nutrisi pada anak bahkan belum memahami prosedur pemenuhan kebutuhan nutrisi pada anak. Penelitian ini bertujuan untuk menganalisa adanya hubungan antara gangguan proses makan dengan sulit makan. Menurut hasil studi pendahuluan yang dilakukan peneliti di Pustu Mimbaan II terdapat 108 orang yang mengalami sulit makan dari 148 balita. Jenis penelitian ini adalah Observasi dengan desain cross sectional, dengan sampel ibu-ibu yang memiliki balita di Pustu Mimbaan II Kecamatan Panji Kabupaten Situbondo.Besar sampel yaitu 108 orang. Pengambilan data dilakukan dengan menggunakan kuesioner. Data yang diperoleh diuji menggunakan chi square dengan tingkat kemaksimalan (α = 0.05) diperoleh hasil nilai 0.081, maka H0 diterima dan H1 ditolak artinya tidak ada hubungan dari gangguan proses makan dengan picky eater (sulit makan). Kata kunci: Gangguan proses makan dan sulit makan